Health information seeking behavior of Filipinos, 45-years-old and above with cardiovascular diseases living in Quezon City - Landicho, Quiella A. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
The rate of mortality caused by cardiovascular diseases continues to grow in the recent years not only in the Philippines but also worldwide. With this, a lot of people with cardiovascular diseases seek health information regarding their conditions. Hence, in an attempt to inhibit the increasing number of cases, and to lessen the mortality rate caused by cardiovascular diseases, it is vital to determine how people search for health information. The purpose of this study is to determine the health information seeking behavior of Filipinos, 45-years-old and above with cardiovascular diseases living in Quezon City.